How informed is declared altruism in clinical trials? A qualitative interview study of patient decision-making about the QUEST trials (Quality of Life after Mastectomy and Breast Reconstruction). Issue 1 (December 2016) - Bidad, Natalie; MacDonald, Lindsay; Winters, Zoë; Edwards, Sarah; Emson, Marie; Griffin, Clare; Bliss, Judith; Horne, Rob
Abstract Background Randomised controlled trials (RCTs) often fail to recruit sufficient participants, despite altruism being cited as their motivation. Previous investigations of factors influencing participation decisions have been methodologically limited. This study evaluated how women weigh up different motivations after initially expressing altruism, and explored their understanding of a trial and its alternatives. The trial was the 'Quality of Life after Mastectomy and Breast Reconstruction' (QUEST) trial. Methods Thirty-nine women participated in qualitative interviews 1 month post-surgery. Twenty-seven women (10 trial decliners and 17 acceptors) who spontaneously mentioned 'altruism' were selected for thematic analysis. Verbatim transcripts were coded independently by two researchers. Participants' motivations to accept or decline randomisation were cross-referenced with their understanding of the QUEST trials and the process of randomisation. Results The seven emerging themes were: (1) altruism expressed by acceptors and decliners; (2) overriding personal needs in decliners; (3) pure altruism in acceptors; (4) 'hypothetical altruism' amongst acceptors; (5) weak altruism amongst acceptors; (6) conditional altruism amongst acceptors; and (7) sense of duty to participate. Poor understanding of the trial rationale and its implications was also evident. Conclusions Altruism was a motivating factor for participation in the QUEST randomised controlled trials where the main outcomes comprised quality of life and allocated treatments comprised established surgical procedures. Women's decisions were influenced by their understanding of the trial. Both acceptors and decliners of the trial expressed 'altruism', but most acceptors lacked an obvious treatment preference, hoped for personal benefits regarding a treatment allocation, or did not articulate complete understanding of the trial. Trial registration QUEST A, ISRCTN38846532 ; Date assigned 6 January 2010. QUEST B, ISRCTN92581226 ; Date assigned 6 January 2010.